Plasma selenoprotein P levels of healthy males in different selenium status after oral supplementation with different forms of selenium - Persson-Moschos, M; Alfthan, G; Åkesson, B (European journal of clinical nutrition, 1998)
To assess changes in selenoprotein P levels in plasma from subjects who had received oral supplements of different selenium forms. The same study group participated in two similar selenium supplementation trials, Trial I in 1981 (Levander et al, 1983) and Trial II in 1987 (Alfthan et al, 1991). During Trial II the mean baseline intake of selenium in Finland was higher compared to that during Trial I (100 and 40 microg/d, respectively), due to a nationwide supplementation of fertilisers which started in 1985. Fifty healthy Finnish men, 36-60 y old. The study group received daily placebo or oral supplements consisting of 200 microg selenium as selenium-enriched yeast, sodium selenate or selenium-enriched wheat (Trial I) or selenium-enriched yeast, sodium selenate or sodium selenite (Trial II). The duration of supplementation periods was 11 (Trial I) and 16 (Trial II) weeks. In Trial I the mean plasma selenoprotein P values in all the supplemented groups increased significantly, approaching a plateau at 2 weeks and reaching maxima at 4 weeks (mean increase 34%, P < 0.05). In Trial II the mean selenoprotein P levels of the supplemented groups were not significantly different from each other or from the placebo group at the start or at any time point of the supplementation period. At a low selenium status the selenoprotein P levels increased in a similar fashion after supplementation with different forms of selenium, but at a high selenium status no significant effects of supplementation with the same amount of selenium were observed. No differences in selenoprotein P levels were observed for inorganic and organic selenium supplements.